Aclidinium bromide/formoterol fumarate as a treatment for COPD: an update. (2nd September 2021) - D'Urzo, Anthony D.; Singh, Dave; Donohue, James F.; Chapman, Kenneth R.; Wise, Robert A.
ABSTRACT: Introduction : Aclidinium/formoterol is a long-acting muscarinic antagonist (LAMA) and long-acting β2 -agonist (LABA) dual bronchodilator used as a maintenance treatment for patients with chronic obstructive pulmonary disease (COPD). The efficacy of aclidinium/formoterol has been demonstrated consistently in patients with moderate-to-severe COPD versus placebo and monocomponents, with a comparable safety profile. Areas covered : This review examines recent research findings that expand our understanding of the impact of aclidinium/formoterol on the burden of COPD. Reviewed outcomes include improvements in lung function, respiratory symptoms, health-related quality of life, exercise tolerance, exacerbation rates, and clinically important deteriorations. In addition, the reported cardiovascular safety of aclidinium and current LAMA/LABA treatment recommendations are discussed. Expert opinion : Aclidinium/formoterol reduces disease burden in patients with COPD, including those that are treatment-naïve, without a significant increase in safety risk compared with monotherapies. Furthermore, evidence supports an improvement in lung function over a 24-hour period with aclidinium/formoterol treatment versus monotherapy and placebo, which may offer an advantage over some once-daily LAMA/LABA combinations. In summary, the recent evidence discussed in this review adds weight to the use of LAMA/LABA combinations as an initial therapy for certain patients newly diagnosed with COPD.